2013
DOI: 10.1109/jsac.2013.130920
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Network Secrecy

Abstract: Abstract-Secrecy is essential for a variety of emerging wireless applications where distributed confidential information is communicated in a multilevel network from sources to destinations. Network secrecy can be accomplished by exploiting the intrinsic properties of multilevel wireless networks (MWNs). This paper introduces the concept of distributed network secrecy (DNS) and develops a framework for the design and analysis of secure, reliable, and efficient MWNs. Our framework accounts for node spatial dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 59 publications
(59 reference statements)
0
27
0
Order By: Relevance
“…Therefore, according to (6), (16) and (17), at very high levels of the power, proposed scheme outperforms the previous scenario in terms of the secrecy capacity but it approaches an upper bound due to the location of the eavesdropper.…”
Section: Enhancing Secrecy Capacity Via Phase Shifting Schemementioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, according to (6), (16) and (17), at very high levels of the power, proposed scheme outperforms the previous scenario in terms of the secrecy capacity but it approaches an upper bound due to the location of the eavesdropper.…”
Section: Enhancing Secrecy Capacity Via Phase Shifting Schemementioning
confidence: 87%
“…(17) According to (16) and (17), it is obvious that γ E,P S < γ E which results in enhancement of secrecy capacity. Therefore, based on Subsection II-D it can be concluded that C s < C s,P S .…”
Section: Enhancing Secrecy Capacity Via Phase Shifting Schemementioning
confidence: 99%
“…Moreover, the information rate loss due to the path overlapping is larger in NLOS scenarios than in LOS scenarios, because there are more MPCs in the former scenarios. 13 Finally, Fig. 4(b) shows the intrinsic information rate as a function of the transmission bandwidth for different SNRs.…”
Section: R(rmentioning
confidence: 99%
“…In a network setting, spatial distribution of nodes plays an important role, and the Poisson point process (PPP) is used to investigate wireless networks with secrecy [34]- [39]. 2 We advocate the exploitation of wireless network intrinsic properties (e.g., network interference) to strengthen communication secrecy.…”
mentioning
confidence: 99%